Cervical giant immature teratoma in a newborn: A challenge for survival - Nagarjuna Kumbha; Allu Rohita; Sarweswar Porca Reddy; Ambati Karuna Sagar (Wolters Kluwer Medknow Publications, 2019)
Teratomas are a conglomerate of heterogenous cells arising from totipotent germ cells. Cervical teratomas occur 1 per 20,000 to 40,000 live births constituting 1.6-9.3% of all paediatric teratomas . They can present antenatally with cervical mass or polyhydramnios and postnatally with respiratory distress and facial disfigurement. Complete excision of the tumour prevents malignant transformation. Timing of the surgery is based on severity of airway compromise. Surgical outcome and survival depend on pre-existing pressure effects, operative injuries to the vital structures and also co-existing comorbidities. One such complicated case of giant cervical teratoma is described here.